Status Nasab dan Hak Waris Anak Sumbang dalam Perspektif Hukum Perdata dan Hukum Islam - Meidezella; Dwi Wahyuni; Ali Munib (Policy and Law Journal, 2025)
A child born out of wedlock refers to a child conceived from a relationship prohibited by law due to close blood relations between a man and a woman. The existence of such a child raises complex legal issues, particularly concerning lineage (nasab) and inheritance rights, both under civil law and Islamic law. This study aims to analyze and compare the lineage status and inheritance rights of children born out of wedlock under Indonesian civil law and Islamic law. The research method employed is normative legal research with a comparative approach, involving the review of legislation, legal doctrines, and relevant literature. The findings indicate that both legal systems share the principle that the biological father-child relationship is not legally recognized. Under civil law, a child born out of wedlock has no inheritance rights, and recognition is limited to the provision of necessary maintenance. Meanwhile, in Islamic law, a child born out of wedlock is treated like a child of zina (illicit sexual relationship), having lineage and inheritance rights only with the mother and her family. Thus, it can be concluded that both legal systems restrict the inheritance rights of children born out of wedlock, while still emphasizing the moral and humanitarian obligations of parents to fulfill the basic rights of the child.